Comparison of natural versus artificial cycles for endometrial preparation prior to frozen embryo transfer - Tyagitha, Galuh Anindya; Nuryanto, Kartiwa Hadi; Pratama, Gita; Maidarti, Mila; Harzif, Achmad Kemal; Sumapraja, Kanadi; Lestari, Silvia Werdhy; Ampri, Irfan Arieqal Hatta; Talya, Natasha; Yanfaunas, Atika Mahira (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundThe endometrial preparation phase preceding embryo transfer assumes pivotal significance in achieving optimal endometrial receptivity and ensuring the success of pregnancy. The natural cycle (NC) and artificial cycle (AC) are the preferred methods for many in vitro fertilization (IVF) specialists. The objective of this study was to compare the difference between NC and AC in women undergoing frozen-thawed embryo transfer (FET) after IVF. MethodsA cross-sectional study was conducted involving 150 adult women who underwent FET with a single autologous blastocyst stage embryo in a 5-year period (2014-2019). Bivariate analysis was conducted to discern implantation and pregnancy rates associated with NC and AC for endometrial preparation. Multiple logistic regression was used to assess the association between endometrial preparation and clinical outcomes while adjusting for potential confounders. ResultsOf the 150 subjects meeting study criteria, 19 underwent NC, while 131 underwent AC for endometrial preparation. Natural cycle exhibited a higher biochemical pregnancy rates compared to AC (89.5% vs. 53.4%; p=0.003). Artificial cycle is a significant determinant for biochemical pregnancy rates compared to NC (aOR: 0.132;95% CI: 0.028 – 0.623; p=0.010) ConclusionIn women undergoing FET, NC resulted in higher biochemical pregnancy rates compared to AC. However, clinical pregnancy rates and ongoing pregnancies rates did not exhibit significant disparities between NC and AC. Future studies will hopefully further illuminate which protocol is most suitable for the individual patient. Further multi-center randomized clinical trials are needed to confirm the relationship between biochemical pregnancy rates and NC.